Clinicopathological characteristics of early gastric cancer with different level of undifferentiated component and nomogram to predict lymph node metastasis - Li, Chenyu; Xie, Suling; Chen, Dan; Zhang, Jingwen; Zhang, Ning; Mu, Jinchao; Gong, Aixia (Frontiers in Surgery, 2023)
Background: Few studies showed that mixed type early gastric cancer (EGC) relates to higher risk of lymph node metastasis. We aimed to explore the clinicopathological feature of GC according to different proportions of undifferentiated components (PUC) and develop a nomogram to predict status of lymph node metastasis (LNM) in EGC lesions. Methods: Clinicopathological data of the 4375 patients who underwent surgically resection for gastric cancer in our center were retrospectively evaluated and finally 626 cases were included. We classified mixed type lesions into five groups (M1:0%0.05). Conclusion: PUC level should be considered as one of the predicting risk factors of LNM in EGC. A nomogram that predicts the risk of LNM in EGC was developed.